Characterization of Zeolites from Tasikmalaya, Indonesia, and Its Application for Ammonium Removal - Kurniawan, Teguh; Mandalagiri, Nuryoto Levina; Kustiningsih, Indar (ASEAN Journal for Science and Engineering in Materials, 2022)
The objectives of the study were to characterize natural zeolites from Cikalong, Tasikmalaya, Indonesia, and test for ammonium removal. Characterization was performed by using X-ray fluorescence (XRF), X-ray diffraction (XRD), and Scanning Electron Microscope (SEM). According to XRF analysis, the ratio of Si/Al was 6.8. The XRD pattern revealed that the zeolites were mordenite dominant phase. The SEM images showed the needles shape of mordenite typical morphology. Ammonium removal test was performed in the batch reactor with a variation on natural zeolite mass loading and adsorption time. Various isotherm models, i.e., Langmuir, Langmuir-Vageler, Freundlich, and Tempkin were fitted with the kinetic data by using optimization of the sum of the least square method. The Langmuir-Vageler model was best fitted with the error sum of squares 0.01. Furthermore, the study on kinetic models such as Lagergren’s 1st order, Pseudo 2nd order, Elovich, and Intraparticle diffusion was fitted with the ammonium adsorption isotherm data by using optimization of the sum of the least square method. The Pseudo 2nd order showed the smallest error sum of squares 0.007.